Development and characterization of a novel sodium alginate based active film supplemented with Lactiplantibacillus plantarum postbiotic - Akman, Perihan Kubra; Kutlu, Gozde; Tornuk, Fatih (ELSEVIER, 2023)
In this study, sodium alginate based biodegradable films were prepared by the supplementation with postbiotics of Lactiplantibacillus plantarum subsp. plantarum (L. plantarum) W2 strain and the effect of probiotics (probiotic-SA film) and postbiotics (postbiotic-SA film) incorporation on physical, mechanical (tensile strength and elongation at break), barrier (oxygen and water vapor permeability), thermal and antimicrobial properties of the films was investigated. The pH, titratable acidity and brix of the postbiotic was 4.02, 1.24 % and 8.37, respectively while gallic acid, protocatechuic acid, myricetin and catechin were the major phenolic compounds. Mechanical and barrier properties of the alginate-based films were improved by probiotic or postbiotic supplementation while postbiotic showed a more pronounced (P < 0.05) effect. Thermal analysis showed that postbiotics supplementation increased thermal stability of the films. In FTIR spectra, the absorption peaks at 2341 and 2317 cm  1 for probiotic-SA and postbiotic-SA edible films confirmed the incorporation of probiotics/postbiotics of L. plantarum W2 strain. Postbiotic supplemented films showed strong antibacterial activity against gram-positive (L. monocytogenes, S. aureus and B. cereus) and gram-negative bacterial (E. coli O157:H7) strains while probiotic-SA films did not show any antibacterial effect against the test pathogens. SEM images revealed that the supplementation of postbiotics provided a rougher and rigid film surface. Overall, this paper brought a new perspective for development of novel active biodegradable films by incorporation of postbiotics with improved performance.
Keywords: Probiotics; Postbiotics; Lactiplantibacillus plantarum W2; Sodium alginate; Biodegradable film; CELL-FREE SUPERNATANT; LACTOBACILLUS-RHAMNOSUS GG; EDIBLE FILMS; PHYSICOCHEMICAL CHARACTERIZATION; ANTIMICROBIAL ACTIVITY; PROTEIN FILMS; FOOD; CONSUMPTION; DIVERSITY; Biochemistry & Molecular Biology; Chemistry; Polymer Science